Salivary pellicles - Lindh,L. (2015)
© 2014 by S. Karger AG, P.O. Box, CH-4009 Basel (Switzerland). All rights reserved. The salivary pellicle is a thin acellular organic film that forms on any type of surface upon exposure to saliva. The role of the pellicle is manifold, and it plays an important role in the maintenance of oral health. Its functions include not only substratum protection and lubrication, but also remineralization and hydration. It also functions as a diffusion barrier and possesses buffering ability. Not only the function, but also the formation, composition and stability of the pellicle are known to be highly influenced by the physicochemical properties of both substrata and ambient media. In this chapter, we discuss these aspects of salivary pellicles, an area where research has boomed in the past years partly because of the application of experimental techniques often reserved for more traditional surface science studies.